2010
DOI: 10.1097/brs.0b013e3181b63673
|View full text |Cite
|
Sign up to set email alerts
|

Cement Filling Control and Bone Marrow Removal in Vertebral Body Augmentation by Unipedicular Aspiration Technique

Abstract: The aspiration technique combined with a new cannula design improved the uniformity of filling. The aspiration technique helps in removal of the displaced bone marrow or tumor tissue. The aspiration applied with the new cannula requires only a single incision. Thus, it does not result in an increased invasiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…The boundary of the surrogates simulated the vertebral shell which confines the flow and controls the intravertebral pressure, significantly affecting the filling pattern [28]. This is consistent with previous studies in which Loeffel et al [13] sealed their surrogates with a reusable acrylic enclosure, while Baroud et al [11] and Mohamed et al [14] coated their surrogates with a 1 mm layer of acrylic cement to mimic the vertebral shell. The boundary including the inlet and the flow exit points were kept constant for all the surrogates within this study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The boundary of the surrogates simulated the vertebral shell which confines the flow and controls the intravertebral pressure, significantly affecting the filling pattern [28]. This is consistent with previous studies in which Loeffel et al [13] sealed their surrogates with a reusable acrylic enclosure, while Baroud et al [11] and Mohamed et al [14] coated their surrogates with a 1 mm layer of acrylic cement to mimic the vertebral shell. The boundary including the inlet and the flow exit points were kept constant for all the surrogates within this study.…”
Section: Discussionsupporting
confidence: 78%
“…Also, the surface wettability of the surrogates matches that of bone and the presence of the marrow substitute simulates the two-phase flow that occurs within the vertebral body. In previous studies, Bohner et al [8] and Loeffel et al [13] both used melted cow butter, whereas Baroud et al [11] and Mohamed et al [14] both used a water/gelatin solution. A true representation of the rheological properties of human red bone marrow present within the cancellous bone is extremely important as such properties significantly affect the cement flow behaviour [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be shown that (jet)-lavage does not cause cardiovascular reaction in combination with contralateral application of vacuum and can significantly decrease the embolic load in sheep [30]. Similar results, significant reductions of cement leakage, were found by Mohamed et al [33], using an unipedicular aspiration technique (without lavage) in a vertebroplasty model.…”
Section: Discussionsupporting
confidence: 73%
“…[14][15][16][17][18] However, this is just one part of a wider requirement to understand how the cement flows within cancellous bone and accurately predict the cement placement within the vertebral body, which has been identified as a critical parameter in the biomechanical behaviour of the construct post-augmentation. 19,20 The rheological properties play a crucial role in the cement flow behaviour during injection and within a porous structure such as cancellous bone.…”
Section: Introductionmentioning
confidence: 99%